The measurement of exhaled carbon monoxide in healthy smokers and non-smokers - Deveci, SE; Deveci, F; Açik, Y; Ozan, AT (W B Saunders Co Ltd, 2004)
The measurement of exhaled carbon monoxide (CO) level may provide an immediate, non-invasive method of assessing smoking status. The aims of this study were to use a portable CO monitor to compare the exhaled CO levels in established smokers and non-smokers. The exhaled CO levels were measured in 322 subjects (243 healthy smokers, 55 healthy non-smokers, 24 passive smokers) who applied to healthy stand during the spring student activity of Firat University in Elazig. Exhaled CO concentration was measured using the EC50 Smokerlyser. The mean exhaled CO level was 17.13 +/- 8.50 parts per million (ppm) for healthy smokers and 3.61 +/- 2.15 ppm for healthy non-smokers, and 5.20 +/- 3.38 ppm for passive smokers. There were significant positive correlation between CO levels and daily cigarette consumption, and CO levels and duration of smoking in healthy smokers (r = +0.550, P<0.001, r = +0.265, P<0.001, respectively. Spearman's test). When smokers and non-smokers were looked at as a whole, a cutoff of 6.5 ppm had a sensitivity of 90% and specificity of 83%. In conclusion, exhaled CO level provides an easy, an immediate way of assessing a subject's smoking status. (C) (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: exhaled carbon monoxide; smoking; passive smoking